Effect of Bean Extract (Phaseolus vulgaris L) to LDL and Ox-LDL and Relation of Ox-LDL on LOX-1 Gene Polymorphism 3'UTR - Shahrul Rahman (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2014)
Background: Atherosclerosis is an inflammatory disease that leads to the emergence ofaterom plaque, which causes thickening of the blood vessel wall. Acute myocardialinfarction (AMI) is caused by rupture of atherosclerotic plaques that trigger acutethrombosis cause total occlusion of the coronary artery. Initiating event in atherosclerosisis the change LDL into oxidized (OxLDL). Activation of OxLDL would be mediated byvarious scavenger receptors, such as LOX-1. Consumption of legumes can reduce the riskof coronary heart disease. This study want to find out whether the kidney beans that areincluded in legumes have efficacious as preventive risk of atherosclerosis.Objective: To prove that kidney bean extract can lower LDL and OxLDL plasma in LOX-1gene polymorphism 3'UTR188C/T as preventive risk of atherosclerosis.Research methods: laboratory experiments with phytochemical test, test kidney beanextract effect with a dose of 400 mg, 800 mg dan 1200 mg per day on lipid profile andplasma levels of OxLDL by Enzyme -linked Immunosorbent Assay (ELISA), test3'UTR188C/T gene polymorphism with restriction enzyme.Results: The results of the phytochemical screening kidney bean extract contain activecompounds such as alkaloids, saponins, flavonoids, triterpenoids/steroids, and glycosides.LDL found decrease in all treatment groups with the highest decrease in the 800 mggroup, although not significantly. But found elevated levels of OxLDL in all treatmentgroups with the highest increase were also in the group of 800 mg. Most study participantswere genotype CT.Conclusion: It has been produced kidney bean extract in the form of extracts condensedthat has met the standards. Kidney bean extract can lower LDL cholesterol. Althoughkidney bean extract can increase plasma Ox-LDL, further research needs to be done tosee the existence of an increase in the levels of OxLDL. Participants with TT genotype hadhigher levels of plasma OxLDL than other genotypes.